2014
DOI: 10.1097/rli.0000000000000052
|View full text |Cite
|
Sign up to set email alerts
|

Metallic Artifacts From Internal Scaphoid Fracture Fixation Screws

Abstract: Both MDCT and FPCT standard-dose acquisition showed comparatively less metal-induced artifacts and better overall image quality compared with FPCT low-dose and both CBCT acquisitions. Flat-panel CT may provide sufficient image quality to serve as a versatile CT alternative for postoperative imaging of internally fixated wrist fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 30 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…From a technical point of view, FPCT imaging should result in more artifacts than MDCT imaging because of the technical set-up and a higher amount of scatter radiation. 17 Consecutively, the majority of papers reports more artifacts in FPCT compared with MDCT, 4 , 5 , 18 although few data suggest different results. 19 , 20 These diverging results can probably be explained due to differences in density, configuration, and positioning of the tested material.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a technical point of view, FPCT imaging should result in more artifacts than MDCT imaging because of the technical set-up and a higher amount of scatter radiation. 17 Consecutively, the majority of papers reports more artifacts in FPCT compared with MDCT, 4 , 5 , 18 although few data suggest different results. 19 , 20 These diverging results can probably be explained due to differences in density, configuration, and positioning of the tested material.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that MDCT has a higher contrast resolution, produces fewer image artifacts, and has a lower scan time. 4 , 5 Nonetheless, the FPCT provides a higher spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…During the past years flat panel detector CT within the angiography suite has increasingly been used to rule out peri-interventional complications such as intracranial hemorrhage or to visualize implanted materials, and also to serve as a non-invasive method for high-resolution imaging of cerebrovascular structures and pathologies during follow-up. 4–7 Since metal artifacts strongly limit the diagnostic value of follow-up studies after clipping or coiling, and also in other fields of radiology, 8 9 the introduction of algorithms for metal artifact reduction (MAR) was an important step forward in providing images of diagnostic value in patients with metallic implants. 10 11 …”
Section: Introductionmentioning
confidence: 99%
“…5,29,30 However, when metallic components are present in the bones studied, standard-dose CT scans have better image quality, with fewer artifacts, than lowdose CT scans. 31…”
mentioning
confidence: 99%